2018
DOI: 10.1056/nejmoa1806842
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Epinephrine in Out-of-Hospital Cardiac Arrest

Abstract: In adults with out-of-hospital cardiac arrest, the use of epinephrine resulted in a significantly higher rate of 30-day survival than the use of placebo, but there was no significant between-group difference in the rate of a favorable neurologic outcome because more survivors had severe neurologic impairment in the epinephrine group. (Funded by the U.K. National Institute for Health Research and others; Current Controlled Trials number, ISRCTN73485024 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
433
3
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(491 citation statements)
references
References 35 publications
11
433
3
11
Order By: Relevance
“…Several experimental studies reported that although adrenaline increased cerebral perfusion pressure, it paradoxically impaired cerebral microvascular blood flow, indicating its potential to worsen brain injury after ROSC . Consistent with these studies, Perkins et al reported in a recent randomised trial of adrenaline in out‐of‐hospital cardiac arrest that the increase in ROSC rate with the use of adrenaline did not translate into an increase in survival with good neurologic outcome because more survivors had severe neurologic impairment in the adrenaline group . Although pralidoxime facilitated ROSC by potentiating the pressor effect of adrenaline in the present study, it may potentiate the adverse effects of adrenaline as well, thereby offsetting the beneficial effects of pralidoxime on ROSC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several experimental studies reported that although adrenaline increased cerebral perfusion pressure, it paradoxically impaired cerebral microvascular blood flow, indicating its potential to worsen brain injury after ROSC . Consistent with these studies, Perkins et al reported in a recent randomised trial of adrenaline in out‐of‐hospital cardiac arrest that the increase in ROSC rate with the use of adrenaline did not translate into an increase in survival with good neurologic outcome because more survivors had severe neurologic impairment in the adrenaline group . Although pralidoxime facilitated ROSC by potentiating the pressor effect of adrenaline in the present study, it may potentiate the adverse effects of adrenaline as well, thereby offsetting the beneficial effects of pralidoxime on ROSC.…”
Section: Discussionmentioning
confidence: 92%
“…Adrenaline remains the mainstay medication in the treatment of cardiac arrest. Clinical trials have shown that adrenaline increases rates of restoration of spontaneous circulation (ROSC) and survival to hospital admission . However, the vast majority of patients with out‐of‐hospital cardiac arrest still do not achieve ROSC or survive to hospital admission despite receiving adrenaline, warranting the need for novel therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines recommend the use of epinephrine and amiodarone, both of which improve short-term outcomes in out-of-hospital cardiac arrest, but there is limited evidence supporting substantial neurological improvement when these medications are used. 59,60 Given the differences between in-hospital and out-of-hospital cardiac arrest (Table 1), especially the much earlier administration of drugs in the in-hospital setting, it is unclear whether findings from studies of out-of-hospital cardiac arrest apply to in-hospital cardiac arrest. For in-hospital events, early administration of epinephrine in patients with a nonshockable rhythm is associated with better outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, in a trial of 8014 patients with OHCA, randomized to epinephrine or placebo, 30‐day survival was higher in the former group (3.2% [ n = 130] vs 2.4% [ n = 94]). After subgroup analysis, the survival benefit (OR = 2.10) was noted only in patients with a nonshockable initial rhythm; the subgroup known to have the worse outcomes . This being said, negative prognostic factors, notably lack of initial shockable rhythm could be regarded as markers of advanced stage of cardiac arrest and patients with these criteria would benefit most from intubation and/or vasoactive resuscitative drugs.…”
Section: Discussionmentioning
confidence: 99%